Co-relation of legal unification and harmonization (International relations and international law Journal, 2016)
In this article the author tried to give a definition of the terms"unification" and "harmonization", considered their forms and methods. In addition, we conducted a detailed analysis of views on the correlation of the terms "unification" and "harmonization". Despite the fact that institutions of unification and harmonization investigated and applied in practice for a long time, today there is no precise definition. The opinions of the researchers in this field are different, but the concepts and conclusions offered by them are similar.
Keywords: unification; harmonization; legal norm; the national legislation; the legal system